P016 Steroid prescribing and risk of adrenal insufficiency: an audit of giant cell arteritis cases. (23rd April 2022) - Ellis, Jessica; Ibbotson, Lucy; Mulhearn, Ben; Skeoch, Sarah
Abstract: Background/Aims: On 13th August 2020 a joint National Patient Safety Alert (NPSA) was issued regarding the introduction of a new steroid emergency card to support recognition and treatment of adrenal crisis. Providers must ensure patients are assessed regarding their risk of adrenal insufficiency, and where appropriate issued a steroid emergency card. Rheumatology departments frequently prescribe patients long-term courses of steroids as treatment for inflammatory disease, placing these patients at risk of secondary adrenal insufficiency. We identified new giant cell arteritis (GCA) patients as a well-defined patient group at high risk for secondary adrenal insufficiency. As such we decided to audit our steroid prescribing practice in these patients, in light of the NPSA. Methods: All new confirmed cases of GCA treated at the Royal United Hospital for Rheumatic Diseases between 1/1/19 and 31/12/20 were identified (n = 90). Standards for audit were developed in accordance with the NPSA advice. In addition to issuing emergency cards we assessed whether patients were informed of the risk of adrenal insufficiency, symptoms suggestive of adrenal insufficiency and sick day rules. A thorough review of all available clinical notes was undertaken for all patients to assess compliance with the above standards. Data collection was completed on 16/8/21. Results: No patients were given steroid emergency cards at their first visit; four were given cards during measured follow up. 5/90 patients were given written information about risk of adrenal insufficiency at their first visit; a further six were informed during measured follow up. 1/90 patients were given written information about signs/symptoms of adrenal insufficiency at their first visit; a further six were informed during measured follow. No patients were given written information about sick day rules at their first visit; a further 9 were informed during measured follow up. Qualitative record review suggested that inconsistencies in follow up pathways may have compounded these issues. Conclusion: Existing departmental practices to inform GCA patients regarding the risk of secondary adrenal insufficiency, and ensure provision of steroid emergency cards are inadequate. Our audit only measured in house documentation, it is possible that primary care prescribers may also be addressing some of these areas. We have already instigated several measures to address these issues. Our GCA service has been amended as part of a wider service improvement project - frequency of follow has improved and dedicated GCA clinics created. Patients are given standardised written information on steroids and a personalised reduction plan. Education sessions have been provided to medical and nursing teams. Wider trust initiatives including electronic prescribing of emergency cards have been introduced, and their incorporation into our service is ongoing. Re-audit is planned in 6 months (January 2022). Disclosure: J. Ellis: None. L. Ibbotson: None. B. Mulhearn: None. S. Skeoch: None.